1978
DOI: 10.1115/1.3426198
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of Jaw Growth

Abstract: Growth of the human face occurs in unequal amounts at various areas. This results in relative motion of the upper and lower jaws. Relative motion creates changes in facial appearance and dental occlusion. Orthodontic treatment seeks to therapeutically use or alter this relative motion. Most existing orthodontic analyses have interpreted facial growth as translatory in nature. The analysis introduced in this paper is based on applying kinematic fundamentals—that is, poles of rotation and fixed and moving centro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Modal vibration test data ,such as stuctural natural frequencies and mode shapes ,can characterize the state of the structure [1]and using them to determine global defects has been investigated [2,3]. Numerous studies have indicated that an increase in structural damage reflects a decrease in natural frequencies of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Modal vibration test data ,such as stuctural natural frequencies and mode shapes ,can characterize the state of the structure [1]and using them to determine global defects has been investigated [2,3]. Numerous studies have indicated that an increase in structural damage reflects a decrease in natural frequencies of the structure.…”
Section: Introductionmentioning
confidence: 99%